2016
DOI: 10.3807/josk.2016.20.5.567
|View full text |Cite
|
Sign up to set email alerts
|

Highly Birefringent and Dispersion Compensating Photonic Crystal Fiber Based on Double Line Defect Core

Abstract: We propose a highly birefringent and dispersion compensating photonic crystal fiber based on a double line defect core. Using a finite element method (FEM) with a perfectly matched layer (PML), it is demonstrated that it is possible to obtain broadband large negative dispersion of about -400 to -427 ps/(nm.km) covering all optical communication bands (from O to U band) and to achieve the dispersion coefficient of -425 ps/(nm.km) at 1.55µm. In addition, the highest birefringence of the proposed PCF at 1.55 μm i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…Dispersion is a measure of the temporal broadening of the optical pulse and it is one of the main sources of penalty for efficient transmission of optical signals. A PCF of high Birefringence and negative dispersion compensation is important in optical amplification as it maintains linear polarisation and useful for double Raman gains and sensing 21 . Furthermore, research has shown that achieving high birefringence, high nonlinearity and negative dispersion can be useful for polarization control in fiber optic sensors, telecommunication applications and broadband dispersion compensation in high-bit-rate transmission systems 22 .…”
Section: Numerical Analysis Of Photonic Crystal Fiber Of Ultra-high Bmentioning
confidence: 99%
See 1 more Smart Citation
“…Dispersion is a measure of the temporal broadening of the optical pulse and it is one of the main sources of penalty for efficient transmission of optical signals. A PCF of high Birefringence and negative dispersion compensation is important in optical amplification as it maintains linear polarisation and useful for double Raman gains and sensing 21 . Furthermore, research has shown that achieving high birefringence, high nonlinearity and negative dispersion can be useful for polarization control in fiber optic sensors, telecommunication applications and broadband dispersion compensation in high-bit-rate transmission systems 22 .…”
Section: Numerical Analysis Of Photonic Crystal Fiber Of Ultra-high Bmentioning
confidence: 99%
“…Furthermore, research has shown that achieving high birefringence, high nonlinearity and negative dispersion can be useful for polarization control in fiber optic sensors, telecommunication applications and broadband dispersion compensation in high-bit-rate transmission systems 22 . A lot of work has been reported recently to achieve high birefringence, high nonlinearity and dispersion management through the use of elliptical holes around the core 23,24 , using different shapes of air holes other than circular in or around the core [25][26][27] , defective core 21 , doping the core with gas or liquid and hybrid cladding 28,29 , double cladding 22 , dual core photonic bandgap 30 , triangular lattice 31 and other shapes of air hole rings apart from the widely used hexagonal lattice [32][33][34][35] . Rhombic and elliptical hole PCFs have been presented 26 to achieve birefringence (B) of 8 × 10 -3 and Confinement loss(CL) of 5 × 10 -4 dB/m at 1.55 µm.…”
Section: Numerical Analysis Of Photonic Crystal Fiber Of Ultra-high Bmentioning
confidence: 99%
“…The result shows an increase in the confinement loss as the wavelength increases with the value of 1.55 μm being 2.767 × 10 −5 dB m −1 at Λ = 2.3 μm which is better than [10,[33][34][35].…”
Section: Verification Of Confinement Lossmentioning
confidence: 91%
“…A square structure of PCF [33] with seven air rings in the cladding and a circular PCF [34] has been demonstrated to exhibit birefringence of 10 −2 with a negative chromatic dispersion and confinement loss of less than 10 −3 at 1.55 μm. However, the dispersion is not tuneable and the air holes in the core are complex.…”
Section: Introductionmentioning
confidence: 99%
“…Due to this difference, the coupling between x-polarized and y-polarized modes decreases significantly [23]. Under these circumstances, the state of polarization of incident light can be maintained along the PCF provided that the light is coupled to only one of the polarized modes [26,27]. The birefringence is defined as [26,27]…”
Section: Birefringencementioning
confidence: 99%